Pengaruh Motivasi, Reward Dan Pengembangan Karir Terhadap Produktivitas (Studi Kasus Pada Karyawan CV Arjuna Flora) - Murziq Zayyiq Sarroz; Afi Rachmat Slamet; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the Effect of Motivation, Reward and Career Development on Productivity in CV Arjuna Flora Employees. The population in this study was all employees of CV Arjuna Flora. The method in data collection uses a questionnaire with a sample number of 46. The independent variables in this study are motivation, reward, and career development. The independent variable is productivity. The analysis method uses multiple linear analysis processed through SPSS Statistics IMB 25. The results of this study simultaneously show that Motivation, Reward and Career Development have a positive and significant effect on Productivity. Partially, Motivation, Reward and Career Development have a positive and significant effect on Productivity. Keywords: Motivation, Reward, Career Development and Productivity.